Cardiomyopathy with Restrictive-Hypertrophic Phenotype and Initial Morphological Diagnosis “Amyloidosis” as a Manifestation of Danon Disease in a Woman - O. V. Blagova; E. A. Kogan; V. P. Sedov; Yu. A. Lutokhina; A. V. Nedostup; A. V. Ott; L. M. Dashinemaeva; E. V. Zaklyazminskaya (Рациональная фармакотерапия в кардиологии)
Aim. To analyze the difficulties of diagnosis and the clinical features of the Danon disease in women.Results. An observation of Danon disease in a woman aged 18 years with an uncomplicated family history is presented. The early development of atrial fibrillation (at the age of not more than 15 years) in combination with atrioventricular blockade against the background of regular sports was not attracted due attention for 3 years. The examination revealed: a moderate degree of left ventricular hypertrophy (up to 17 mm), its diffuse nature and simultaneous involvement of the right ventricle, signs of heart failure due to severe restrictive disorders with preserved ejection fraction. Cardiac magnetic resonance imaging data (non-specific late gadolinium enhancement) became the basis for the assumption of amyloidosis and the implementation of a myocardial biopsy. An erroneous diagnosis of cardiac amyloidosis according to myocardial biopsy was refuted during a second study, the PAS reaction revealed signs of storage disease. The diagnosis of Danon disease was verified using DNA diagnostics (c.731delG mutation was detected). Due to the presence of unsustained paroxysmal ventricular tachycardia and a high calculated risk of sudden death, cardioverter-defibrillator was implanted. The analysis of literature data on the frequency and the manifestation of Danon disease in women, the place of this disease in the structure of the causes of myocardial hypertrophy is given.Conclusion. Atrial fibrillation at a young age and left ventricular hypertrophy syndrome can develop due to primary myocardial diseases not well known in the practice of a cardiologist. They require an in-depth diagnostic search; their identification is critical for determining treatment tactics and prognosis.